The Effect of Acidic pH on Growth Kinetics, Biomass Productivity, and Prima-ry Metabolite Contents of Euglena sp. - Nurafifah, Istini; Hardianto, Muhammad Andhi; Erfianti, Tia; Amelia, Ria; Maghfiroh, Khusnul Qonita; Kurnianto, Dedy; Siswanti, Dwi Umi; Sadewo, Brilian Ryan; Putri, Renata Adaranyssa Egistha; Suyono, Eko Agus (UI Scholars Hub, 2023)
Euglena is a microalga with the potential to be an environmentally friendly renewable energy resource. The pH value is a crucial factor in micro-algal cultivation. Changes in pH affect the growth and development of microalgae, including the production of biomass and primary metabolites, such as proteins, carbohydrates, and lipids. In this study, Euglena sp. was grown on Cramer-Myers medium and subjected to various acidic conditions. This study aimed to determine the effect of pH on the growth kinetics, biomass, carbohydrate, lipid, and protein contents of Euglena sp. The Euglena sp. culture was optimized at various pH values of 2.5, 3.5, and 4.5. The results were analyzed by one-way analysis of variance at a 95% confidence level, followed by Duncan’s multiple range test. As results, Euglena sp. had the best growth rate, the greatest biomass, and the highest carbohydrate, protein, and lipid contents at pH 3.5 compared to the other pH conditions. The average biomass in the pH 3.5 treatment was 1.600 ± 0.229 g/L, and the carbohydrate, protein, and lipid contents were 5.983 ± 0.056 g/L, 0.196 ± 0.023 µg/mL, and 0.300 ± 0.020 g/L, respectively.